Spontaneous CSF otorrhea in cases of Mondini’s dysplasia: a rare cause of recurrent bacterial meningitis - Bihani, Ameya; Shah, Keya; Hardikar, Priyanka; Dokhe, Yogesh; Dabholkar, Jyoti (International Journal of Contemporary Pediatrics, 2017)
Inner ear anomaly is rare developmental anomaly with Mondini’s dysplasia being the most common. The perilymphatic fistula cause due to high pressure condition in anomalous inner ear result into CSF otorrhea which become a tract for bacteria to reach central nervous system and cause recurrent meningitis. We are presenting 3 cases of Mondini’s dyaplasia which had CSF leaking into middle ear cleft which was diagnosed with HRCT of temporal bone with cisternography and MRI cisternography and were managed successfully with surgical repair by trans-mastoid approach.